100 Evaluation of an innovative emotional resilience syllabus to support students in caring for complex patients in clinical settings. (22nd November 2019) - Gowers, Nicola; Hudson, Natalie; Tonkin, Tabitha; George, Isabella De
Abstract : GOSH patients have multiple comorbidities, complexities and multifaceted conditions. Therefore, the nursing care required can be demanding and requires a certain level of emotional resilience. As students are new to this role, they are yet to develop the emotional intelligence needed. Due to time constraints and a complex caseload, practitioners don't always have the time or resources to offer such support. Hence, The Strong Student Seminar Series was created. The Strong Student Seminar Series was developed following an increase in students requiring 1:1 pastoral support. Whilst there was already mindfulness training being delivered, it was recognised that more tailored training was needed to ensure the students could develop their own coping mechanisms. The syllabus design sees different tools, models and topics being explored, allowing students the protected time to develop their understanding of complex issues and how they can manage the impact of these both personally and professionally. Small working groups allow students psychological safety and individualised support, encouraging group participation and peer support through multiple activities. Overall evaluation of the syllabus for the year was conducted using an online survey. On analysis of 100 responses, it showed 85% of students found the sessions 'extremely useful'. Feedback was predominantly positive, with students finding the sessions relaxed, allowing them to speak openly and feel supported. Students also felt that it gave them the tools to discuss concerns and escalate accordingly. Based on feedback, it is evident that the presence of an emotional resilience syllabus is greatly valued. It is evident that it plays a significant role in helping students cultivate their own coping mechanisms and encourages them to value and develop their own health and wellbeing. Thus, enabling them to cope with the increasing demands of nursing complex patients, as well as the additional pressures on the current NHS nursing workforce.